Model kepuasan pelanggan bagi laman web e-runcit - A. Kahar, Aidil Suraya (2008)
E-Retail, the short form of Electronic Retailing is a process where the goods are sold on the Internet. E-Retail is one of the examples of the Business-to-Consumer (B2C) businesses conducted online. E-Retail benefits consumer, organization and community. Even though this method benefits all parties, the e-retail website which provides customer satisfaction has not been accorded similar attention. By performing this project, the characteristics of a good e-retail website and what should have been on the website have been identified. They can be categorised into three key elements; the basic element function, additional function and design layout of the website. After taking into account the key elements, the model that will ultimately satisfy the customer will be developed. This is aimed at guiding retailer to develop a website that can support and increase customer satisfaction as well as increase the buying transaction that can generate profit to the retailers that utilises the e-retail as their business medium.